Survey of the History and Applications of Saffron - Motahareh Asgari; Qun Yu; Meghdad Abdi; Guang-Li Du; Yun-Hui Shen; Er-Liang Wang (Wolters Kluwer Health/LWW, 2022)
Abstract. Fan Hong Hua (李时珍 saffron) is a natural product that has long been used in food and dye industries and fortreating various disorders. Saffron has a long history of applications in traditional Chinese medicine, following its introduction to China in 1979. According to the theory of traditional Chinese medicine, saffron is sweet, slightly cold in nature and enters heart and liver meridians. Moreover, this spice can invigorate blood circulation, eliminate blood stasis, cool blood and eliminate heat toxins. Saffron has been used to treat asthma, phlegm, insomnia, Alzheimer's disease, depression, fright, shock, hemoptysis, heartburn, and pain. Among the almost 70 bioactive ingredients of saffron, major constituents of this herb include safranal, crocin, and crocetin, which are responsible for the unique taste and color of saffron. These ingredients have been investigated using modern pharmaceutical research methods as potential therapeutics to treat disorders such as Alzheimer's disease, cardiovascular diseases, cancer, digestive system disorders, ocular issues, and COVID-19 infections. However, focus and emphasis on understanding the pharmacological effects of saffron in treating diseases are required. This article briefly reviews the history, cultivation processes, different qualities properties, and traditional and modern applications of this unique herb.